Barriers and facilitators of implementation of new antibacterial technologies in patient care: an interview study with orthopedic healthcare professionals at a university hospital - Lieve Vonken; Gert-Jan de Bruijn; Annika Noordink; Stef Kremers; Francine Schneider (BMC, 2024)
Abstract Background Antimicrobial resistance is a major global health threat. Therefore, promising new antibacterial technologies that could minimize our dependence on antibiotics should be widely adopted. This study aims to identify the barriers and facilitators of the adoption of new antibacterial technologies in hospital patient care. Methods Semi-structured interviews, based on the Consolidated Framework for Implementation Research, were conducted with healthcare professionals related to the orthopedics department of an academic hospital in The Netherlands. Results In total, 11 healthcare professionals were interviewed. Scientific evidence for the effectiveness of the technology was the most explicitly mentioned facilitator of adoption, but other (often contextual) factors were also considered to be important. At the level of the inner and outer setting, high costs and lacking coverage, competition from other firms, and problems with ordering and availability were the most explicit perceived barriers to adoption. Participants did not collectively feel the need for new antibacterial technologies. Conclusions Barriers and facilitators of the adoption of new antibacterial technologies were identified related to the technology, the hospital, and external factors. The implementation climate might have an indirect influence on adoption. New antibacterial technologies that are scientifically proven effective, affordable, and easily obtainable will most likely be adopted.